Environmental science : a Canadian perspective - Freedman, Bill; Dalhousie University. Libraries; BC Open Textbook Project; BCcampus (Dalhousie University Libraries Digital Editions, 2018)
"This textbook is intended to provide the core elements of a curriculum for teaching environmental science at the introductory level in Canadian colleges and universities. This book is suitable for students beginning a program in environmental science, environmental studies, or sustainability. It is also appropriate for arts students who require a science elective, and for science students who require a non-major elective. This book was written from the ground-up to provide Canadian information and examples. This national context is integrated throughout the text, along with North American and global data that provide a broader perspective."--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on December 11, 2018).
Keywords: Environmental sciences -- Textbooks; Electronic books